Reconstruction of the Aortic Arc through Left Thoracotomy in Patients with Isolated Coarctation and Aortic Arch Hypoplasia - Y. Truba; I. Dziuryi; O. Motrechko; O. Golovenko (Ukrainian Journal of Cardiovascular Surgery, 2021)
Background. The choice of surgical approach for the reconstruction of aortic arch hypoplasia is a rather controversial issue. Traditionally, left lateral thoracotomy is used to correct aortic coarctation with hypoplasia of one or more arc seg-ments. However, in recent years, more and more clinics have begun widespread use of median sternotomy for the surgical treatment of aortic arch hypoplasia. The purpose of the research was to analyze the immediate and long-term results of surgical treatment of isolated hypoplasia of the aortic arch in infants through left thoracotomy.Materials and methods. From 2010 to 2019, 159 infants with coarctation and hypoplasia of one or more segments of the aortic arch underwent reconstruction of the aortic arch at the National Amosov Institute of Cardiovascular Surgery of the NAMS of Ukraine and Ukrainian Children’s Cardiac Center. The study included only patients with biventricular physiology and subsequent biventricular correction. There were 108 male patients (68%) and 51 female patients (32%).The mean age of the patients was 2.4 ± 0.9 months, the mean body weight was 4.7 ± 2.0 kg. The main method of diagnosis, i.e. determining the defect and assessing the immediate and long-term results, was echocardiographic examination. The study group consisted of 155 patients (97.5%) in whom the reconstruction of the aortic arch was performed through left thoracotomy, in the remaining 4 patients (2.5%) the intervention was performed through median sternotomy.Results. In-hospital mortality was 0.6% (n = 1). The average time of the operation was 126 ± 40 minutes, the aortic cross-clamp time was 24.7 ± 5.1 minutes. The mean duration of mechanical ventilation after the surgery was 41 ± 15.9 hours.The mean follow-up period ranged from 1 month to 13 years. There were no deaths in the long-term period. Ten (6.4%) patients developed aortic arch restenosis in the postoperative period. In 8 patients, the narrowing was treated by endovascular dilatation. Two patients underwent repeated aortic arch repair using median sternotomy. There were no cases of compression of the trachea, main bronchi, neurological complications in the follow-up period.Conclusions. Reconstruction of the aortic arch hypoplasia through left thoracotomy is an effective and safe treatment option in infants associated with good immediate and long-term results. The study indicates that this surgical strategy can be used in most patients with hypoplasia of the isthmus and distal aortic arch.